Looking for Alibrandi - Marchetta, Melina, 1965- (New York : A.A. Knopf, 2006)
During her senior year in a Catholic school in Sydney, Australia, seventeen-year-old Josie meets and must contend with the father she has never known.
"A Borzoi Book"--T.p. verso.
"Originally published in Australia by Penguin Books Australia in 1992"--T.p. verso.
School Library Journal
Wilson's Junior High School
Wilson's Senior High School
Young Adult.
Keywords: Catholic schools -- Fiction; Fathers and daughters -- Fiction; High schools -- Fiction; Schools -- Fiction; Catholic schools -- Fiction; Fathers and daughters -- Fiction; High schools -- Fiction; Schools -- Fiction; Catholic schools -- Fiction; Father-daughter relationship -- Fiction; High schools -- Fiction; School stories; Australia -- Fiction; Sydney (N.S.W.) -- Fiction; Australia -- Fiction; Sydney (N.S.W.) -- Fiction; Australia -- Fiction; Sydney (N.S.W.) -- Fiction